Real-Time PCR Assays for Rapid Identification of Common Aphanomyces astaci Genotypes - Di Domenico, Marco; Curini, Valentina; Caprioli, Riccardo; Giansante, Carla; Mrugała, Agata; Mojžišová, Michaela; Cammà, Cesare; Petrusek, Adam (Frontiers in Ecology and Evolution, 2021)
Crayfish plague is an acute disease caused by the oomycete Aphanomyces astaci that seriously impacts the populations of European native crayfish species. The introduction of non-indigenous crayfish of North American origin and their wide distribution across Europe has largely contributed to further spread of crayfish plague in areas populated by indigenous species. Tracking A. astaci genotypes may thus represent a useful tool to investigate the crayfish plague natural history in its European range, as well as the sources and introduction pathways of the pathogen. In this study we describe the development of genotype-specific TaqMan real-time PCR assays to distinguish the five genotype groups of A. astaci previously defined by their distinct RAPD patterns. The method was evaluated using DNA extracts from pure A. astaci cultures representing the known genotype groups, and from A. astaci-positive crayfish clinical samples collected during crayfish plague outbreaks recently occurred in Central Italy and Czechia. Group A, B, D and E assays are extremely specific, while group C assay (not yet documented from crayfish plague outbreaks) showed cross-reactivity with A. fennicus. The unusual A. astaci genotype Up documented from crayfish plague outbreaks in Czechia is detected by the group B real-time PCR, while the genotype rust1 described in USA from Faxonius rusticus is detected by the group C assay. Analysis of additional markers (such as sequencing of the nuclear internal transcribed spacer or mitochondrial ribosomal subunits) may complement these cases when the real-time PCR-based genotyping is not conclusive. Overall, the method represents a robust and fast tool to genotype A. astaci during outbreaks or latent infections.